Facile synthesis of multifunctional La1−xSrxMnO3@Au core–shell nanoparticles for biomedical applications. Issue 116 (5th November 2015) - Liu, Xiao; Liu, Hong-Ling; Fang, Ning; Li, Xue-Mei; Guo, Wei-Hua; Wu, Jun-Hua; Zhao, Mei-Xia
Abstract : Multifunctional high-performance La1− x Sr x MnO3 @Au core–shell nanoparticles were synthesized by nanoemulsion with polymers, showing sharp Curie transition, excellent amphiphilic dispersibility and optical properties as well as biocompatibility. Abstract : Multifunctional high-performance La1− x Sr x MnO3 @Au core–shell nanoparticles were successfully synthesized by a modified nanoemulsion method with the assistance of poly(ethylene glycol)- block -poly(propylene glycol)- block -poly(ethylene glycol) (PEO-PPO-PEO). X-ray diffraction (XRD) and transmission electron microscopy (TEM) analyses confirm the structure and morphology of the nanoparticles. The measurements obtained using ultraviolet-visible light absorbance spectrometry (UV-vis), vibrating sample magnetometry (VSM), and a physical property measurement system (PPMS) demonstrate that the nanoparticles exhibit a surface plasmon resonance (SPR) absorption band around 561 nm from nanostructured Au and a unique magnetic nature at room temperature. Particularly, a sharp, tight phase transition from ferromagnetic to superparamagnetic states is observed in a free-standing La1− x Sr x MnO3 nanoparticle system for the first time with a Curie temperature around room temperature. The cytotoxicity of the nanoparticles was studied for safe biomedical applications using an MTT assay. The results show that the La1− x Sr x MnO3 @Au core–shell nanoparticles with lower cytotoxicity, well-defined magnetic and optical properties are promising for optical, magnetic, and biomedical application.